Protecting depositors and promoting financial stability in South Africa : is there a case for the introduction of deposit insurance? - Ngaujake, Uahatjiri (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2004)
Banks play a pivotal role in economic growth and development of all countries and therefore the stability of the banking system is a vital goal of bank supervisors. Banks act as delegated monitors of depositors' funds and this relationship, like all principal-agent relationships, presents agency problems. In the case of banks agency problems arise because depositors cannot accurately assess the financial health of banks due to the asymmetry of information existing between banks and depositors. Because banks possess private information on their borrowers, which depositors cannot access, it exposes depositors to risk of loss of deposits in cases of bank failures originating from nonrepayment of such loans. This asymmetry of information also exposes banks to runs by depositors and these runs can lead to bank failures with devastating effects for the financial system and the economy at large. It is for this reason that banks are regulated and supervised more than other institutions. Bank failures are a worldwide phenomenon and South Africa is no exception as evidenced by historical and recent bank failures in South Africa. This thesis investigates the desirability of introducing an explicit deposit insurance scheme in South Africa as a means of protecting small, unsophisticated depositors who are almost always the losers when banks fail, and promoting financial stability. The study finds that bank failures in South Africa are mainly attributable to mismanagement of banks, liquidity problems and fraud. Bank failures as a result of the aforementioned reasons have led to depositors losing their deposits in South Africa. The absence of a clearly defined depositor protection scheme in South Africa, the inadequacy of the hitherto implicit guarantee system to protect depositors, and the poor record of the South African Reserve Bank in bank failure resolution, form the basis of the conclusion of the study, i.e., there is a case for the introduction of deposit insurance in South Africa. In order to assist South African policymakers in designing an effective deposit insurance scheme for the country, the thesis further provides a guide on how the most important design features of deposit insurance should be handled. This is in an attempt to ensure that the moral hazard problem inherent in deposit insurance is overcome.
Keywords: Banks and banking -- South Africa; Bank deposits -- South Africa; Bank failures; Banks and banking -- State supervision; Deposit insurance; Consumer protection -- South Africa